(untitled) (Cadernos de Psicologia Social do Trabalho, 2012)
This paper presents results from a research which investigated the effects of work on the health of Federal Justice officials at Porto Alegre. The demand emerged from the Union of Workers of the Federal Justice of Rio Grande do Sul (Sintrajufe-RS), due to increased complaints with regard to the health of these servants. A structured questionnaire was used, the Self Report Questionnaire (SRQ-20), in order to survey the prevalence of minor psychiatric disorders and the methodology of Work Psychodynamics, with a methodological model of researchaction. The results obtained point out that the main problem is related to a lack of recognition to the work performed by these professionals. Issues of disrespect with regard to their activity and solitary work were also reported by the group. One suggests a discussion/meeting space involving the workers, the coordination, and the judge's representation, with the participation of Psychology professionals, characterizing a permanent action.